Endowment banks as a mechanism to activate the endowment of money in Algeria - mousa salmi (Journal of Excellence for Economics and Management Research, 2021)
This topic deals with the study of the possibility of establishing endowment banks based on the permissibility of endowment of money in Islamic jurisprudence, within its organizational framework, which is based on defining the concept of the endowment bank and how to establish these banks and how to manage them And through its applied framework, using the experience of the Turkish Endowment Bank and contemporary applied economic studies, and trying to use them in order to find a practical framework for activating the endowment of money in the Algerian legal and economic system